Who Owns Tonga: Dialogues with Sefita Hao’uli, Kalafi Moala, and Melino Maka - Brown Pulu, Teena (Te Kaharoa, 2014)
<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">“Who owns Tonga?” asked Sefita Hao’uli. “We do. The people,” I quickly pitched back. But do we really? Quietly I second guessed myself after blurting out an idealistic reply. It might have sufficed the correct response in a liberal democracy where by one general election registered voters elected all their members of parliament. But in the Kingdom of Tonga’s 2014 election year the dread squatting on my conscience murmured the monarchy and nobility owned Tonga, while ordinary people leased meagre pieces from the upper class for a price. <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">What social and economic cost did the country pay for not having a liberal democracy? By having nine nobles’ seats in parliament where thirty-three title and estate holders, all male, elected their class representatives to Tonga’s legislative assembly, did this impede the political system from democratic reform? This last essay in a series of four dialogues with Sefita Hao’uli, Kalafi Moala, and Melino Maka prods a recurring sore in the side of democratic politics and liberal notions that all citizens are created equal by modern constitutional arrangements. How can these principles be practiced under a parliamentary structure that starkly exhibits partiality towards noblemen over and above commoners?